KEPEMIMPINAN SPIRITUAL GURU DALAM PEMBENTUKAN KARAKTER PESERTA DIDIK DI KABUPATEN TASIKMALAYA JAWA BARAT - Bela Elqaweliya (Jurnal Pengabdian Masyarakat Multidisiplin, 2022)
ABSTRACT Teacher Spiritual Leadership in Character Building Students. (Case Study at the Plus Vocational High School (SMK Plus) Serba Bakti Foundation Pondok Pesantren Suryalaya Tasikmalaya, West Java). Keywords: spiritual leadership, teacher character building, vocational high school students The crisis occurred in various fields, starting from the economic, political, social, cultural and moral fields, including the education sector. Schools as a means of transferring knowledge and culture to students are an important part of improving the morale of the nation's children. Teachers as agents of change really need their role to succeed in character education programs in schools. The focus of this program is to focus on the spiritual leadership of teachers. In detail, the focus of this program discusses (1) the characteristics of the teacher's spiritual leadership in forming the character of students (2) the character values ​​formed in students (3) the process of teacher spiritual leadership in forming the character of students (4) the results of the teacher's spiritual leadership. in the formation of the character of students. The method used in this activity is in the form of training and education regarding the spiritual leadership of teachers in shaping the character of students. The result of this training activity is an increase in teacher knowledge in the field of spiritual leadership which is evaluated using modules and collection of lesson plans that are used to be taught and applied to students in the implementation of learning in the school environment. Keywords: Teacher Spiritual Leadership, Character, Students